Editor's Highlight: High-Throughput Functional Genomics Identifies Modulators of TCE Metabolite Genotoxicity and Candidate Susceptibility Genes. (21st August 2017) - De La Rosa, Vanessa Y.; Asfaha, Jonathan; Fasullo, Michael; Loguinov, Alex; Li, Peng; Moore, Lee E.; Rothman, Nathaniel; Nakamura, Jun; Swenberg, James A.; Scelo, Ghislaine; Zhang, Luoping; Smith, Martyn T.; et al.
Abstract: Trichloroethylene (TCE), an industrial chemical and environmental contaminant, is a human carcinogen. Reactive metabolites are implicated in renal carcinogenesis associated with TCE exposure, yet the toxicity mechanisms of these metabolites and their contribution to cancer and other adverse effects remain unclear. We employed an integrated functional genomics approach that combined functional profiling studies in yeast and avian DT40 cell models to provide new insights into the specific mechanisms contributing to toxicity associated with TCE metabolites. Genome-wide profiling studies in yeast identified the error-prone translesion synthesis (TLS) pathway as an import mechanism in response to TCE metabolites. The role of TLS DNA repair was further confirmed by functional profiling in DT40 avian cell lines, but also revealed that TLS and homologous recombination DNA repair likely play competing roles in cellular susceptibility to TCE metabolites in higher eukaryotes. These DNA repair pathways are highly conserved between yeast, DT40, and humans. We propose that in humans, mutagenic TLS is favored over homologous recombination repair in response to TCE metabolites. The results of these studies contribute to the body of evidence supporting a mutagenic mode of action for TCE-induced renal carcinogenesis mediated by reactive metabolites in humans. Our approach illustrates the potential for high-throughput in vitro functional profiling in yeast to elucidate toxicity pathways (molecular initiating events, key events) and candidate susceptibility genes for focused study.